Nonlinear Robust Backstepping Control Based MPPT for Photovoltaic System - Meskini Mohammed Amine; Khafallah Mohamed; Hassoune Abdelilah; Diouri Anas (EPJ Web of Conferences)
The energy produced by the photovoltaic generator (PVG) depends on different factors, and it is mainly affected by climatic conditions, i.e. temperature and solar irradiation. In order to extract the maximum available power from the PVG, it must operate at its maximum power point (MPP), which changes continuously throughout the day. This paper proposes the design approach of a non-linear Maximum Power Point Tracking (MPPT) based Backstepping controller. The developed controller controls the boost converter and imposes the PVG to operate at its MPP by generating the cycle ratio corresponding to the voltage at the Maximum Power Point (VMPP) generated by the Incremental Conductance algorithm (INC). Simulation results of the controller demonstrate the effectiveness of the proposed controller in fast MPP tracking with superior dynamic performance and disturbance rejection capabilities compared to conventional controller.